2021
DOI: 10.2196/22148
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approach to Decision Making for Insulin Initiation in Japanese Patients With Type 2 Diabetes (JDDM 58): Model Development and Validation Study

Abstract: Background Applications of machine learning for the early detection of diseases for which a clear-cut diagnostic gold standard exists have been evaluated. However, little is known about the usefulness of machine learning approaches in the decision-making process for decisions such as insulin initiation by diabetes specialists for which no absolute standards exist in clinical settings. Objective The objectives of this study were to examine the ability of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Del Parigi et al [56] showed that ML (Random Forest) could be used to determine the predictors of the highest improvement in glycemic control for an individual patient from the data pooled from randomized controlled trials. In addition, Fujihara et al [81] have shown that ML (Neural Networks) can aid clinicians to decide, with high prediction accuracy, when to initiate an insulin regimen for their patients with Type 2 diabetes. Crutzen et al [82] employed a collection of algorithms to identify patients with type 2 diabetes at an increased risk of hypoglycaemia in primary care.…”
Section: Potential Role In Diabetes Mellitusmentioning
confidence: 99%
“…Del Parigi et al [56] showed that ML (Random Forest) could be used to determine the predictors of the highest improvement in glycemic control for an individual patient from the data pooled from randomized controlled trials. In addition, Fujihara et al [81] have shown that ML (Neural Networks) can aid clinicians to decide, with high prediction accuracy, when to initiate an insulin regimen for their patients with Type 2 diabetes. Crutzen et al [82] employed a collection of algorithms to identify patients with type 2 diabetes at an increased risk of hypoglycaemia in primary care.…”
Section: Potential Role In Diabetes Mellitusmentioning
confidence: 99%
“…Various models are used to identify drugs associated with the risk of DILI at the preclinical stage [28]. Machine learning models have demonstrated strong predictive power and retained a simple form for communication with researchers [29][30][31][32][33][34][35][36][37][38][39]. XGBoost is a boosting ensemble machine learning algorithm that integrates a few classification and regression trees models to form a strong classifier [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…However, approximately 35% to 40% of patients worldwide initiating the use of an oral antihyperglycemic drugs did not receive the recommended initial therapy [49][50][51]. Table 1 summarizes studies of the predictability of the use of antihyperglycemic medications using artificial intelligence [52][53][54][55][56][57]. Liu et al [52] investigated prescriptions in 82 patients and reported that 80.2% of recommendations generated from guidelines coincided with the medication classes (metformin, insulin secretagogues or α-glucosidase inhibitors, thiazolidinediones, dipeptidyl peptidase-4 inhibitors [DPP-4I], insulin) from their real prescriptions by K-Nearest Neighbors.…”
Section: Machine Learning For Diabetes Carementioning
confidence: 99%
“…We recently elucidated the ability of machine learning models and determined whether artificial intelligence might assist clinicians in deciding on the initial insulin therapy for type 2 diabetes mellitus in clinical practice. We recruited 4,860 participants who received initial monotherapy by diabetes specialists [ 56 , 58 ]. We found no superiority of performance of machine learning over logistic regression.…”
Section: Machine Learning For Diabetes Carementioning
confidence: 99%